PRELIMINARY EXAMINATION OF HERBAL EXTRACTS ON THE INHIBITION OF HELICOBACTER PYLORI - Guzeldag, Gulcihan; Kadioglu, Lutfiye; Mercimek, Aysun; Matyar, Fatih (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This review aims at describing the traditional uses, to determine the antimicrobial potential of two different extracts hexan, acetone of the leaves of Citrus unshiu, Citrus sinensis, Citrus limon, Laurus nobilis, Citrus paradisi on clinical strain of H. pylori in a bid to identify potential sources of cheap starting materials for the synthesis of new drugs. H. pylori strain was a culture collection of Hacettepe University, Turkey. The activity was quantitatively assessed on the basis of the inhibition zone, and their activity index was also calculated along with the MIC method. All the plants demonstrated antimicrobial activity against H. pylori with zone of inhibition diameters ranging from 0 - 30 mm and minimum inhibitory concentration (MIC) values ranging from 1:512- 1:4096 dilutions. The results may serve as scientific validation of the ethnomedicinal uses of the Citrus unshiu, Citrus sinensis, Citrus limon, Laurus nobilis, and Citrus paradisi in the treatment of H. pylori-related infections. However, further investigations would be necessary to determine their toxicological properties, in-vivo potencies and mechanism of action against H. pylori.